Sarcoidosis Presenting as Acute Respiratory Distress Syndrome - Bilal Haider Lashari; Ahmad Raza; Vincent Chan; William Ward (Case Reports in Medicine)
Sarcoidosis is a multisystem granulomatous disease of unknown origin. It typically involves the lungs and mediastinal lymph nodes in a chronic fashion. However, acute syndrome has been reported possibly in response to systemic release of proinflammatory cytokines. Acute pulmonary manifestations, especially acute respiratory failure or acute respiratory distress syndrome, remain extremely uncommon in individuals without a prior diagnosis. We present the case of a 41-year-old African American female, who presented with ARDS. An extensive workup into the cause of her illness remained negative, and she subsequently succumbed to her illness. A diagnosis of sarcoidosis was made upon autopsy, after exclusion of other granulomatous illness. The case highlights the need to consider this uncommon diagnosis in patients with unexplained ARDS to guide therapy.